Time management as a main factor influencing outpa-tients satisfaction on quality of service in public health facilities - Shopati, Abner Kukeyinge; Mitonga, Kabwebwe Honore; Shilunga, Anna Kauko (International Journal of Medicine, 2017)
This study aims to explore factors influencing outpatient client satisfaction level with quality of service to recommend friends and family to the three intermediate public health hospitals in Namibia. Reviewing the literature, 14 variables were identified. The items were then reduced using exploratory factor analysis which is evaluated using Principal Axis Factoring with Direct Oblimin rotation. Using exploratory factor analysis, variables were categorized into 8 factors. This model, in the order of effect, identified Total Time Spent in the outpatient department before leaving (in minutes) is the most important predictor of ES (expected satisfaction) values of (0.499), Sum of Medication Communication (0.105), Contact Time with Doctors/Nurses (in minutes) (0.099), Sum of Nurse Communication (0.089), Sum of Doctor Communication (0.049), First Time Visit to this Outpatient Department (0.031), Age groups (0.030) and Facility Name (0.011) is the least important predictor for client to recommend their friends and family to the three intermediate public health care in Namibia. This implies that Total Time Spent in the outpatient department before leaving (in minutes) is the most important predictor of ES by outpatient clients on quality of service perceptions and has the largest impact of recommending friends and family to receive services at the three intermediate public hospitals.